A longitudinal assessment of running economy and tendon properties in long-distance runners - Kubo, K.; Tabata, T.; Ikebukuro, T.; Igarashi, K.; Tsunoda, N. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to investigate longitudinal changes in tendon properties and running economy of long-distance runners (LDRs) in the preparatory periods of track season (TS) and road season (RS). Eleven well-trained LDRs and 6 untrained subjects participated in the present study. In each period, muscle strength, neural activation level, and tendon elongation for both knee extensors and plantar flexors, jump performances, and oxygen consumption during submaximal running velocities were measured. No significant differences observed in any measured variables between the 2 seasons for untrained subjects. For LDRs, the total running distance during 1 month preceding RS (832 ± 95 km) was significantly longer than that during 1 month preceding TS (718 ± 80 km). No significant differences in the muscle strength, neural activation level, and jump performances were found between TS and RS. The stiffness of tendon structures in RS was significantly lower than those in TS for both knee extensors (-14.4%, p = 0.023) and plantar flexors (-16.6%, p = 0.040). At 3 running velocities, the oxygen consumptions in RS were significantly lower than those in TS. These results suggested that the lower oxygen consumption during submaximal running velocities observed in the preparatory period of RS may be attributable to the more compliant tendon structures but not in the neuromuscular characteristics.